Proceedings of Seventh International Conference on APL - APL '75 1975
DOI: 10.1145/800117.803784
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of APL defined functions

Abstract: The content of defined functions in 51APL workspaces are analyzed.The static content, rather than dynamic usage, is given. The two source APL systems were Burroughs APL/700 and IBM APL/360 XM6.This data identifies those portions of the APL language that actually appear in workspaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…One of the findings of the statistical studies on APL programs [5,6,73 was the great disparity in sizeapproximately 10 to I -between typical FORTRAN and APL programs. More specific comparisons between alternate language versions of the same algorithm also bear this out.…”
Section: Design Of the Target Level For Apl Translationmentioning
confidence: 99%
“…One of the findings of the statistical studies on APL programs [5,6,73 was the great disparity in sizeapproximately 10 to I -between typical FORTRAN and APL programs. More specific comparisons between alternate language versions of the same algorithm also bear this out.…”
Section: Design Of the Target Level For Apl Translationmentioning
confidence: 99%
“…Bingham [1] analyzed the contents of 51 APL workspaces to determine the frequency of occurrence of various phrases and combinations of phrases in a large sample of APL programs.…”
Section: Introductionmentioning
confidence: 99%
“…The 11,340 statements generated 104,220 ISUÀFL pseudo^code instructions. A detailed description of the data base contents may be found in (13) in which comparisons with other studies of APL programs (11,12,42) establish the "present sample of programs as being truly representativ APL programs in general." e of…”
Section: Generation Of the Data Basementioning
confidence: 98%
“…Robinson and Torsun (41) did an additional study on the use of FORTRAN. Bingham (11,12) and Saal and Weiss (42) have examined characteristics of APL programs. PL/l has been the target of studies by Elshoff (16,17,18), while features of COBOL usage have been reported by Chevance and Heidet (14) and Salvadori, Gordon, and Capstick (43).…”
Section: Literature Reviewmentioning
confidence: 99%